2022
DOI: 10.1021/acs.jchemed.1c01054
|View full text |Cite
|
Sign up to set email alerts
|

Evaluating the Effectiveness of Organic Chemistry Textbooks for Promoting Representational Competence

Abstract: The goal of this study was to evaluate the effectiveness of organic chemistry textbooks in developing student representational competence skills with eight representations of molecular structure (Lewis structures, Kekulé structures, condensed structures, electrostatic potential maps, skeletal structures, dash–wedge diagrams, Newman projections, and chair conformations). Five commonly used organic chemistry textbooks in the United States were deductively coded with Kozma and Russell’s representational competen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
15
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(15 citation statements)
references
References 32 publications
0
15
0
Order By: Relevance
“…Similarly, Linenberger and Holme (2015) found that biochemistry instructors identify the ability to interpret and generate representations as key skills for their courses, without discussing higher-level skills. The finding that organic chemistry instructors do not teach meta-RC skills might be linked to the fact that meta-RC skills are not taught in organic chemistry textbooks (Gurung et al, 2022); this link is suspected because textbooks often serve as curricular guides and play a critical role in lesson planning and how the material is explained (Tulip and Cook, 1993;Bergqvist and Chang Rundgren (2017)). These findings suggest a gap in the current instruction because according to prior research, it is important to intentionally go beyond simple skills such as the ability to interpret representations and support students in the acquisition of higher-level meta-RC (diSessa, 2004;Scho ¨nborn and Anderson, 2006;Xue and Stains, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…Similarly, Linenberger and Holme (2015) found that biochemistry instructors identify the ability to interpret and generate representations as key skills for their courses, without discussing higher-level skills. The finding that organic chemistry instructors do not teach meta-RC skills might be linked to the fact that meta-RC skills are not taught in organic chemistry textbooks (Gurung et al, 2022); this link is suspected because textbooks often serve as curricular guides and play a critical role in lesson planning and how the material is explained (Tulip and Cook, 1993;Bergqvist and Chang Rundgren (2017)). These findings suggest a gap in the current instruction because according to prior research, it is important to intentionally go beyond simple skills such as the ability to interpret representations and support students in the acquisition of higher-level meta-RC (diSessa, 2004;Scho ¨nborn and Anderson, 2006;Xue and Stains, 2020).…”
Section: Conclusion and Discussionmentioning
confidence: 99%
“…If we want students to interpret, generate, translate between, and use these representations, it makes sense to practice drawing and manipulating them. Indeed, cultivating a “set of skills and practices that allow a person to reflectively use a variety of representations or visualizations, singly or together, to think about, communicate, and act on chemical phenomena” (i.e., representational competence; p 131) has been called out by a number of scholars as fundamental to learning chemistry. , Several studies have demonstrated that instructors too value interpreting, generating, and translating between representations. For example, Linenberger and Holme found that interpreting and generating representations were selected as the two most important visual literacy skills by 494 biochemistry instructors they surveyed .…”
Section: Introductionmentioning
confidence: 99%
“…Organic chemistry courses are famous (or perhaps infamous) for integrating a dizzying array of visualizations meant to represent aspects of chemical systems (e.g., Newman projections, electron pushing mechanisms, reaction coordinate diagrams). 1 If we want students to interpret, generate, translate between, and use these representations, it makes sense to practice drawing and manipulating them. Indeed, cultivating a "set of skills and practices that allow a person to reflectively use a variety of representations or visualizations, singly or together, to think about, communicate, and act on chemical phenomena" 2 (i.e., representational competence; p 131) has been called out by a number of scholars as fundamental to learning chemistry.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Many molecular representations are routinely used in textbooks of introductory chemistry, biochemistry, and organic chemistry, e.g., Lewis structures (or Lewis dot diagrams), condensed structures, dash-wedge diagrams, skeletal structures, space filling diagrams, Newman projections, Haworth projections, Fischer projections, ribbon diagrams for proteins, etc. However, these textbooks occasionally do not provide appropriate support for developing the skills needed to interpret and use these representations . The analysis of two-dimensional (2D) representations in chemistry/biochemistry is a challenge for novices, in which the understanding, manipulation, and translation among the various aforementioned forms remain challenging .…”
Section: Introductionmentioning
confidence: 99%
“…However, these textbooks occasionally do not provide appropriate support for developing the skills needed to interpret and use these representations. 1 The analysis of twodimensional (2D) representations in chemistry/biochemistry is a challenge for novices, in which the understanding, manipulation, and translation among the various aforementioned forms remain challenging. 2 A proactive pedagogical approach must be applied when dealing with some chemistry topics considered difficult for beginners, since these can cause an early loss of interest in this discipline.…”
Section: ■ Introductionmentioning
confidence: 99%